Influence of Surfactant Additives on the Electrolyte Flow Velocity and Insoluble Gas Bubbles Behavior within a Lead-Acid Battery. Issue 12 (24th August 2020) - Nahidi, Saeed; Gavzan, Iraj Jafari; Saedodin, Seyfolah; Salari, Mahmoud; Maddah, Bozorgmehr
Abstract : Improving the flooded-electrolyte batteries performance in fast charging and discharging processes has attracted many researchers. Due to electrochemical reactions during charging and discharging process in these batteries, many insoluble gas bubbles are produced within the electrolyte. These bubbles have a major effect on the performance of the electrodes and the rate of electrochemical reactions. On the other hand, the electrolyte flow rate plays an important role on the performance of the battery. In the present investigation, the effect of surface tension on the production of insoluble bubbles and velocity of electrolyte flow have been investigated experimentally when different types of surfactants are added to the electrolyte. In addition, a Particle Image Velocimetry setup has been used in order to measure the velocity of electrolyte flow and the behavior of bubbles. The results declared that the capacity of battery enhances about 16% and 10% by adding Triton X100 and SDS surfactants, respectively. Hence, the averaged electrolyte velocities during charging process reduces about 11% and 13% when Triton X100 and SDS, repectively; are used as surfactants. Also, the effect of adding different amounts of SDS surfactant on the mean diameter, rising velocity and production rates of bubbles have been illustrated comprehensively.